MATERNAL AND NEONATAL RISKS IN POSTDATE PREGNANCIES DIR LOWER (The Research of Medical Science Review, 2025)
This study investigates the maternal and neonatal outcomes in postdated pregnancies at Timergara Teaching Hospital, focusing on the impact of health status, delivery type, maternal complications, and recovery time. A prospective cohort design was employed, including 100 women with postdated pregnancies. The health status of the participants was categorized into four groups: Diabetic (34%), Healthy (28%), Obese (24%), and Hypertensive (14%). Results indicated that nearly 58% of patients had health conditions that increase the risk of complications in postdated pregnancies, such as diabetes, obesity, and hypertension. C-section deliveries were found to be associated with higher neonatal complications, including Neonatal Asphyxia and Low Birth Weight, compared to Normal deliveries, which showed a lower incidence of Premature births. Furthermore, maternal complications such as Postpartum Hemorrhage, Infection, and Pre-eclampsia were linked with severe delivery complications like Shoulder Dystocia and Uterine Rupture. Analysis of recovery time showed that Obese patients had the longest mean recovery time (4.33 days), while Healthy and Hypertensive patients exhibited similar recovery times (around 4 days). This study emphasizes the importance of managing maternal health conditions to improve both neonatal outcomes and recovery times post-delivery. Further research should focus on interventions to address maternal complications and their impact on both maternal and neonatal health outcomes.